Strategi Digital Marketing pada Pendidikan Sekolah Menengah Kejuruan (SMK) - Haryati, Eka; Safitri2, Camelia (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
The purpose of this study was to analyze the benefits of social media such as WhatsApp, Instagram, TikTok, and websites in increasing the number of students in Vocational High Schools (SMK). The method used was descriptive qualitative with 11 informants, including principals, teachers, and guardians. Data collection was carried out through interviews, observations, and documentation, focusing on the effectiveness of digital marketing, challenges of digitalization, and digital platform strategies. The results of the study showed that digital marketing on social media and websites succeeded in increasing the number of students. However, the implementation of digital marketing is still imperfect due to limited human resources and the need for consistency in scheduling promotional content. This study aims to provide innovation in developing and utilizing digitalization through social media and websites to increase the number of students in educational institutions